Improving the health of workers with a low socioeconomic position: Intervention Mapping as a useful method for adaptation of the Participatory Approach - R. Schaap; F. G. Schaafsma; A. R. Bosma; M. A. Huysmans; C. R. L. Boot; J. R. Anema (BMC, 2020)
Abstract Background Workers with a low socioeconomic position (SEP) have a higher risk for health problems and premature dropout from the workforce. Unfavorable working conditions and unhealthy behaviors are more prevalent among this group of workers. The Participatory Approach (PA), is an evidence-based method to identify and solve problems at the workplace related to health issues of the worker. Health problems among workers with a low SEP are usually caused by an interplay of problems in and outside the workplace. To solve health problems on multiple life domains for workers with a low SEP we aim to adapt this approach to a broader perspective. Methods An Intervention Mapping (IM) protocol was used to adapt the PA. First, a needs assessment was conducted combining literature with data from interviews and focus groups with workers with a low SEP, employers and occupational health professionals (OHPs). Based on the needs assessment a program goal and performance and change objectives were defined, which resulted in methods and practical strategies to solve problems on multiple life domains. Based on the results of these steps, the PA was adapted and an implementation and evaluation plan were developed. Results The needs assessment confirmed that an interplay of problems on multiple life domains affect work functioning and health of workers with a low SEP. Moreover, they perceived difficulties with solving problems or used passive or avoidant coping styles towards these problems. The program goal is to identify and solve problems on multiple life domains that affect healthy functioning at work. To achieve this workers need support from OHPs to solve problems. The PA protocol and materials were adapted using theoretical concepts of the Self-Determination Theory (SDT), which resulted in the Grip on Health intervention. For OHPs a training was developed on how to implement this intervention in practice. The intervention will be evaluated in a pilot implementation study among workers with a low SEP and other relevant stakeholders. Conclusions IM was a valuable tool for the adaptation of the PA to better support workers with a low SEP to improve their work functioning and health from a broader perspective.